Novel characterization of stress corrosion cracks - Lozano-Perez, S (2008)
A multi-scale approach to stress corrosion cracking is presented in this paper. It will be shown that the same crack and, more importantly, the crack tip region can be characterized with surface techniques such as NanoSIMS and EBSD and later prepared for TEM or Atom Probe. This will offer a unique insight into the chemistry and microstructure, proving that the right combination of techniques can provide most of the information needed to correctly understand the mechanisms of crack propagation. © 2008 IOP Publishing Ltd.